La hermenéutica mesiánica de las escrituras entre los primeros discípulos de Jesús - Guijarro Oporto, Santiago, 1957- (2017)
The early Christians frequently used the Hebrew Scriptures to understand, enlighten and explain their own experiences of faith and the events on which such experiences were based. To understand the way in which they used such texts, the article turns to the concept of transtextuality, developed by Gérard Genette, and the different forms in which it is expressed. This model is presented with some examples taken from the books of the New Testament. The article concludes with some remarks concerning the contribution of this particular kind of hermeneutics to current readings of the Bible.
Keywords: Jesucristo; Cristianismo; Hermenéutica